Trastuzumab Deruxtecan in Previously Treated HER2-Positive Breast Cancer - Modi, Shanu; Saura, Cristina; Yamashita, Toshinari; Park, Yeon Hee; Kim, Sung-Bae; Tamura, Kenji; Andre, Fabrice; Iwata, Hiroji; Ito, Yoshinori; Tsurutani, Junji; Sohn, Joohyuk; Denduluri, Neelima; et al. (The New England journal of medicine, 2020)
In this single-group, phase 2 study, the use of trastuzumab deruxtecan resulted in a response in 60% of women with HER2-positive advanced breast cancer who had received a median of six previous lines of therapy. The drug was associated with myelosuppression and gastrointestinal toxicity; interstitial lung disease was reported in 13.6% of the patients.